A systematic review to explore influences on parental attitudes towards antibiotic prescribing in children. Issue 5 (27th October 2017) - Bosley, Helen; Henshall, Catherine; Appleton, Jane V; Jackson, Debra
Abstract : Aims and objectives: To understand the factors influencing parental attitudes towards antibiotic prescribing. Background: Overuse of antibiotics and inappropriate prescribing has resulted in rapid development of antimicrobial resistance (AMR) and is a significant global threat to patient safety. In primary care settings, substantial numbers of antibiotics are prescribed for young children, despite viral nature of illness for which antibiotics are ineffective. Parents play a vital role in decision‐making regarding accessing healthcare services and requesting treatment for their children. Design: A systematic review was conducted in alignment with the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) statement (Moher et al., Systematic Reviews, 4, 2015, p. 1). Methods: The CINAHL, MEDLINE, PsycINFO, The Cochrane Library, BRITISH NURSING INDEX, EMBASE and PUBMED databases were searched for primary research published between 2006–2016. All types of primary research were searched and screened against inclusion criteria. The Critical Appraisal Skills Programme tool was used to appraise identified publications. Quantitative data were summarised descriptively, and qualitative data were thematically analysed. Results: A total of 515 publications were initially screened, and 55 full‐text articles were eligibility assessed. Twenty papers met inclusion criteria. Four main themes were identified: the quality of relationships with healthcare providers, dealing with conflicting messages, rationalising antibiotic use and parental practices informed by past experience. Conclusions: Parents wanted reassurance and advice regarding children's illnesses, had poor antibiotic knowledge and were influenced by personal past experiences. More accessible education, including simple information leaflets, is required. Further research on the influence of culture, ethnicity and socio‐economic factors would be beneficial. Relevance to clinical practice: Healthcare professionals must provide adequate time for reassurance and explanations of decision‐making. Easy‐to‐read information regarding appropriate antibiotic usage should be easily accessible for parents.